(untitled) (Mustansiria Dental Journal, 2018)
The most common congenital missing teeth are the upper lateral incisors. This study is performed to find the frequency of missing upper laterals in the young adult Iraqis and to assess their orthodontic treatment. The sample consists of twenty patients with hypodontia of upper lateral incisors (right and left) out of a thousand patients examined for three years in the orthodontic clinic of the Institute of Medical Technology. Gender distribution for patients was 15 females and 5 males. Age distribution for patients ranged from 15 to 25 years. Full record for the hypodontic patients included: photographs, panoramic x-rays and casts taken before and after orthodontic treatment. The treatment by space closure took more orthodontic treatment time and retention period than by space opening and prosthodontic treatment. The frequency of missing upper lateral incisors is 2% (consisting of 1.5% for females and 0.5% for males).